Brain age gap in neuromyelitis optica spectrum disorders and multiple sclerosis. Issue 1 (10th October 2022) - Wei, Ren; Xu, Xiaolu; Duan, Yunyun; Zhang, Ningnannan; Sun, Jie; Li, Haiqing; Li, Yuxin; Li, Yongmei; Zeng, Chun; Han, Xuemei; Zhou, Fuqing; Huang, Muhua; et al.
Abstract : Objective: To evaluate the clinical significance of deep learning-derived brain age prediction in neuromyelitis optica spectrum disorder (NMOSD) relative to relapsing-remitting multiple sclerosis (RRMS). Methods: This cohort study used data retrospectively collected from 6 tertiary neurological centres in China between 2009 and 2018. In total, 199 patients with NMOSD and 200 patients with RRMS were studied alongside 269 healthy controls. Clinical follow-up was available in 85 patients with NMOSD and 124 patients with RRMS (mean duration NMOSD=5.8±1.9 (1.9–9.9) years, RRMS=5.2±1.7 (1.5–9.2) years). Deep learning was used to learn 'brain age' from MRI scans in the healthy controls and estimate the brain age gap (BAG) in patients. Results: A significantly higher BAG was found in the NMOSD (5.4±8.2 years) and RRMS (13.0±14.7 years) groups compared with healthy controls. A higher baseline disability score and advanced brain volume loss were associated with increased BAG in both patient groups. A longer disease duration was associated with increased BAG in RRMS. BAG significantly predicted Expanded Disability Status Scale worsening in patients with NMOSD and RRMS. Conclusions: There is a clear BAG in NMOSD, although smaller than in RRMS. The BAG is a clinically relevant MRI marker in NMOSD and RRMS.